Mismatch repair deficiency predicts response to HER2 blockade in HER2-negative breast cancer - Nindo B. Punturi (Nature Portfolio, 2021)
Resistance to endocrine treatment in ER+/HER2- breast cancer patients remains a significant clinical problem. Here, the authors demonstrate that loss of the MutL mismatch repair complex can serve as a first-in-class predictive biomarker for combinatorial inhibition of HER2 to overcome the emergence of endocrine treatment resistance.